2019
DOI: 10.3390/molecules24020286
|View full text |Cite
|
Sign up to set email alerts
|

Alcyonacea: A Potential Source for Production of Nitrogen-Containing Metabolites

Abstract: Alcyonacea (soft corals and gorgonia) are well known for their production of a wide array of unprecedented architecture of bioactive metabolites. This diversity of compounds reported from Alcyonacea confirms its productivity as a source of drug leads and, consequently, indicates requirement of further chemo-biological investigation. This review can be considered a roadmap to investigate the Alcyonacea, particularly those produce nitrogen-containing metabolites. It covers the era from the beginning of marine ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 101 publications
(158 reference statements)
0
7
0
Order By: Relevance
“…Marine alkaloids originating from marine organisms are described in the literature, presenting different biological and pharmacological activities. Several studies describe the presence of alkaloids in Alcyonacea coral species, with antiviral, antitumor, antibiotic, and immunomodulatory activities [44]. Similarly, many sponge alkaloids have been identified, and their potential antibiotic, antifungal, antitumor, antileukemic, and antidepressant activities have been described [45][46][47][48][49].…”
Section: Anti-inflammatory Alkaloids Of Marine Organisms: Sources Andmentioning
confidence: 99%
“…Marine alkaloids originating from marine organisms are described in the literature, presenting different biological and pharmacological activities. Several studies describe the presence of alkaloids in Alcyonacea coral species, with antiviral, antitumor, antibiotic, and immunomodulatory activities [44]. Similarly, many sponge alkaloids have been identified, and their potential antibiotic, antifungal, antitumor, antileukemic, and antidepressant activities have been described [45][46][47][48][49].…”
Section: Anti-inflammatory Alkaloids Of Marine Organisms: Sources Andmentioning
confidence: 99%
“…Soft corals (Alcyonacea), formerly known as gorgonian corals, contrast stony corals in that they do no create a calcium carbonate skeleton (Alarif et al, 2019). In a similar study to the Scleractinia coral extract analyses, Radwan et.…”
Section: Alcyonacea (Soft Coral)mentioning
confidence: 95%
“…Blunt and his co-workers reported that the identified marine metabolites estimated to be 31,000 (i.e., 1000 substances per year) [7]. The molecular structures associated, particularly, produced from marine organisms, are varying from low molecular weight to complex form [8,9,10,11,12,13,14]. These metabolites enhance marine invertebrate’s survival by providing chemical defense.…”
Section: Introductionmentioning
confidence: 99%
“…Alcyonacea (Phylum, Cnidaria; class, Anthozoa; subclass, Octocorallia; order, Alcyonacea) constitutes an important group of marine invertebrates, widely distributed in the coral reefs. They are quite numerous throughout the tropical waters, mainly live in the intertidal zones on inner reefs below the stony corals [14]. They are less prone to damage or ailments from collecting and shipping than the stony corals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation